On the path to sustainable energy landscapes? The social shaping of energy landscapes in the face of climate protection measures - Bosch, Stephan; Schmidt, Matthias; Kienmoser, Dominik (ERDKUNDE, 2020)
Potential spatio-temporal patterns of renewable energies that take into account international climate protection strategies have been neither analysed nor visualised exactly in terms of their landscape complexity. Furthermore, it is unclear what land uses would be prevalent in new energy landscapes, due to a lack of restrictions, and which social conflicts would be associated with these land use changes. There is no knowledge at all about the extent to which existing land use, which has emerged from a capitalistic order, affects the achievement of a carbon-neutral and socially just society. It is also not clear how far it is possible to identify alternative spatial patterns of sustainable energy transition by altering spatial restrictions concerning renewable energies. For this reason, we want to model and visualise a regional energy landscape that corresponds to the objectives of the UN Climate Conference in terms of its regional greenhouse gas balance in the electricity sector. In this regard, the study provides a detailed analysis of the landscape transformations that would occur in rural spaces if those values which attempt to link energy transition to the Paris Agreement were to prevail. The analyses reveal that a strict orientation of the expansion of renewable energies towards climate protection goals would strongly mechanise rural areas, thus significantly transforming their social patterns.